2005
DOI: 10.1007/s10562-005-5197-3
|View full text |Cite
|
Sign up to set email alerts
|

Side-chain alkylation of toluene with methanol on Cs-exchanged NaY zeolites: effect of Cs loading

Abstract: The side-chain alkylation of toluene with methanol was studied on Cs-exchanged NaY zeolites containing up to 31% Cs (exchange degree, ED, up to 70%). Formation of styrene and ethylbenzene was significant only on Na(Cs)Y zeolites of ED higher than about 40%. Bimolecular side-chain alkylation reaction would require a proper surface geometric configuration of O d) -Cs + pairs that is achieved only on Cs-rich zeolites. In contrast, the side reaction forming carbon monoxide from methanol increases monotonically wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…The catalysts for side-chain alkylation of toluene with methanol were studied extensively [1,[6][7][8][9][10][11][12][13]. It was reported that a good catalyst for side-chain alkylation should behave the properties of (1) sufficient base strength to dehydrogenate methanol to formaldehyde, (2) stabilization of adsorbed toluene and polarization of its methyl group, and (3) balanced sorption stoichiometry of the reactants [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalysts for side-chain alkylation of toluene with methanol were studied extensively [1,[6][7][8][9][10][11][12][13]. It was reported that a good catalyst for side-chain alkylation should behave the properties of (1) sufficient base strength to dehydrogenate methanol to formaldehyde, (2) stabilization of adsorbed toluene and polarization of its methyl group, and (3) balanced sorption stoichiometry of the reactants [5].…”
Section: Introductionmentioning
confidence: 99%
“…According to the results reported above-mentioned, the X and Y molecular sieves are suitable for the side-chain alkylation of toluene with methanol, because they possess the requirements of a good catalyst for side-chain alkylation [7,9,[15][16][17][18]. Philippou and Anderson [7] studied the surface species on NaX, KX and CsX catalysts for the side-chain alkylation of toluene with methanol by 13 C solid-state NMR with magic-angle spinning (MAS NMR).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, an early study of zeolite X in different alkali forms reported that ring alkylation was preferred over NaX and appeared to be further promoted by the presence of Brønsted acid sites, which could result from modification with boric acid. Along the same line, experiments over partially exchanged NaY catalysts determined a lower threshold of about 60 % to favor side‐chain over ring alkylation …”
Section: Resultsmentioning
confidence: 84%
“…Therefore, it is impossible for both the deoxygenation of lignin-derived phenols and fast catalytic pyrolysis of lignin to directly produce p-/m-xylene with high selectivity (larger than 10%) [24]. Side-chain alkylation of toluene with methanol to form styrene and ethylbenzene was studied and the formation of styrene and ethylbenzene was significant on Na(Cs)Y zeolites of exchange degree higher than about 40% [25]. Gas-phase acylation of phenol with acetic acid to synthesize o-hydroxyacetophenone was studied on solid acids and zeolites [26,27].…”
Section: Introductionmentioning
confidence: 99%